2021
DOI: 10.1038/s41598-021-99942-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological differences in the calcaneus among extant great apes investigated by three-dimensional geometric morphometrics

Abstract: Investigating the morphological differences of the calcaneus in humans and great apes is crucial for reconstructing locomotor repertories of fossil hominins. However, morphological variations in the calcaneus of the great apes (chimpanzees, gorillas, and orangutans) have not been sufficiently studied. This study aims to clarify variations in calcaneal morphology among great apes based on three-dimensional geometric morphometrics. A total of 556 landmarks and semilandmarks were placed on the calcaneal surface t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Nozaki (2021) conducted a comprehensive 3D geometric morphometry study to explore morphological differences in the calcaneus among humans and great apes. The study revealed distinct differences in the calcaneal morphology between species.…”
Section: Discussionmentioning
confidence: 99%
“…Nozaki (2021) conducted a comprehensive 3D geometric morphometry study to explore morphological differences in the calcaneus among humans and great apes. The study revealed distinct differences in the calcaneal morphology between species.…”
Section: Discussionmentioning
confidence: 99%
“…during toe-off, a flat posterior talar facet, and the presence of a large, plantarly positioned lateral plantar process (Boyle et al, 2018;DeSilva et al, 2019;Harper et al, 2021a;Latimer & Lovejoy, 1989;McNutt & DeSilva, 2020;Nozaki et al, 2021;Prang, 2016). These morphological trends relative to general locomotor behaviors have been observed both broadly among extant hominoid genera and at the species-level within the same genera, thus highlighting that the calcaneus is an informative location to investigate form-function relationships.…”
mentioning
confidence: 80%
“…Calcaneal external morphology is quite variable among extant hominoids and is functionally correlated with known locomotor variation (Harper et al, 2021a, 2021b, 2022; Kidd, 1999; Latimer & Lovejoy, 1989; McNutt & DeSilva, 2020; Nozaki et al, 2021; Prang, 2015, 2016; Prang & Tocheri, 2024). For example, more arboreal non‐human hominoids have a cuboid facet that is relatively larger and has a deeper pivot region, two features that have been suggested to increase mobility at the calcaneocuboid joint during inversion and eversion (Gebo, 1992; Harper et al, 2021a, 2021b; Prang & Tocheri, 2024).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations